2011
DOI: 10.1148/rg.317115108
|View full text |Cite
|
Sign up to set email alerts
|

Novel Oncologic Drugs: What They Do and How They Affect Images

Abstract: Targeted therapies are designed to interfere with specific aberrant biologic pathways involved in tumor development. The main classes of novel oncologic drugs include antiangiogenic drugs, antivascular agents, drugs interfering with EGFR-HER2 or KIT receptors, inhibitors of the PI3K/Akt/mTOR pathway, and hormonal therapies. Cancer cells usurp normal signal transduction pathways used by growth factors to stimulate proliferation and sustain viability. The interaction of growth factors with their receptors activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 102 publications
3
52
0
1
Order By: Relevance
“…Systemic chemotherapy plays an important role in treatment of metastatic liver disease, but its role remains limited in the management of hepatocellular carcinoma (1). Molecular-directed chemotherapies for hepatic metastatic disease and advanced hepatocellular carcinoma target specific biologic pathways, such as angiogenesis, tumor metabolism, and tumor proliferation (2). On the other hand, locoregional therapies have the advantage of treating malignant liver tumors without the risk of potential side effects from systemic chemotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic chemotherapy plays an important role in treatment of metastatic liver disease, but its role remains limited in the management of hepatocellular carcinoma (1). Molecular-directed chemotherapies for hepatic metastatic disease and advanced hepatocellular carcinoma target specific biologic pathways, such as angiogenesis, tumor metabolism, and tumor proliferation (2). On the other hand, locoregional therapies have the advantage of treating malignant liver tumors without the risk of potential side effects from systemic chemotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…94 The derived measurements reflect blood volume, perfusion, and the intrinsic composition of tissues, providing information on microvasculature function. 95 This technique is still under development in patients with head and neck cancers, and further research is warranted. 58 As with other functional techniques, its value within a PET/MR protocol appears questionable at this time.…”
Section: Bold Imagingmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) and the quantifiable apparent diffusion coefficient (ADC) detect motion of water within tumor tissues, which has been useful in tumor detection, characterization, and in monitoring response to treatment [11][12][13]. Previous studies have demonstrated that volumetric functional MR imaging can help in accurately assessing tumor response after loco-regional therapy (LRT) in patients with HCC, neuroendocrine liver metastases (NELM), and islet cell liver metastases (ICLM) [14][15][16].…”
Section: Adcmentioning
confidence: 99%